Gambaran Stres Digital pada Remaja Awal - Emaniar, Rosa; Utami, Rahayu Hardianti (Lembaga Yasin AlSys, 2023)
Current use of digital media and the internet can contribute to stress. So this research aims to see how digital stress looks in early adolescents. This type of research is quantitative with descriptive methods. The population in this study were early adolescents at junior high school (SMP) education level. The sampling technique uses Nonprobability Sampling. The research results showed that 107 people (39.3%) had low digital stress and 165 subjects (60.7%) had high digital stress. In conclusion, this research shows that early adolescents have high digital stress.